Explaining the Relationship of Organizational Health and Employee Depression with Productivity of Personnel) A case study: Sporting and Youth Organizations Personnel in Isfahan Province) - Zeinab MONDALIZADEH; Ehsan SHAKERI (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract   Introduction: Today, the employee productivity is a crucial topic to achieve the organization goals. In this regard, considering the organizational health and employee depression by managers is an important issue in organizational productivity. So, the purpose of this study was to investigate the relationship between organizational health and depression with the productivity of employees of sports and youth departments in Isfahan province and to present a structural equation model. Methods: In this descriptive-analytical study, a partial least squares approach was applied for modeling. The research instruments were Hershey and Goldsmith (1980) Productivity Questionnaire, Hui and Fieldman (1996) Organizational Health Questionnaire, and Beck Depression Inventory (1961). Validity of the questionnaire was confirmed by experts and the reliability of the questionnaires was appropriate. The statistical population included employees of the sports and youth departments of Isfahan province (387 people). The statistical sample size was calculated based on the number of research factors based on the PL approach. As a result, 90 people were appointed and 78 complete questionnaires were collected and returned. Cluster random sampling method was used. Results: The results showed that organizational health had a positive and significant effect on job productivity (p /0 0.01), but depression had a negative effect on job productivity that was not significant. Depression also had a negative effect on organizational health, but this effect was not significant. Conclusion: The ability of the organization to maintain and improve organizational stability and improve this ability leads to improving the productivity of employees of sports and youth departments. In this regard, it is suggested that managers and supervisors of sports organizations emphasize the importance of communication with and among employees to improve organizational health and emphasize organizational psychological issues to improve productivity